General chemistry - Ebbing, Darrell D.; Gammon, Steven D. (Brooks/Cole Cengage Learning, 2013)
This textbook is used for the comprehensive general chemistry course taught primarily to biology, engineering, chemistry and other science majors. This new edition has been substantially revised to meet the rapidly changing instructional demands of general chemistry professors.